Properties of novel PMMA‐co‐EHA bone cements filled with hydroxyapatite. Issue 4 (17th October 2013) - Ferreira, Bárbara J.M. Leite; Barroca, Natalia B.; Lopes, Poliana P.; Daniel‐da‐Silva, Ana L.; Helena, Maria; Fernandes, V.; Correia, Rui N.
<x xml:space="preserve">Abstract</x> To design bone cements with predictable intraoperative and postoperative behavior, researchers must understand how cement formulations affect the polymerization reaction and specially the properties of the end product. In this study, a bioactive filler (commercial hydroxyapatite, HA) was incorporated into poly(methyl methacrylate)‐co‐ethyl hexyl acrylate (PMMA‐co‐EHA) matrices to prepare new bone cement formulations. The new PMMA‐co‐EHA/HA composites were obtained by varying the relative contents of the monomers, MMA, and EHA. The resulting composites were evaluated in terms of the curing parameters, water uptake and weight loss in phosphate buffer solution and mechanical properties. The results obtained showed that incorporation of 25% HA particles induced major changes in the final properties of the bone cements comparing with the unfilled parent matrices. In particular, the peak temperature decreased and the setting time and the bending elastic modulus increased in all formulations containing HA particles. Composites with low EHA content exhibited a decrease in strength after HA incorporation, which was attributed to the poor interfacial adhesion between the components of the composites. Additionally, the immersion results showed that the amount of 25% HA (regarding the total mass) in the composites was not enough to induce in vitro bioactive properties in the materials. POLYM. COMPOS., 35:759–767, 2014. © 2013 Society of Plastics Engineers